THEORETICAL AND PRACTICAL ASPECTS OF MONITORING OF REGION’S SOCIO-ECONOMIC DEVELOPMENT PROCESSES - Yakubiv , V. M.; Popadynets , N. M.; Maksymiv , Yu. V. (The actual problems of regional economy development, 2017)
The article defines the nature of socio-economic development processes monitoring in a region on the basis of systematization of scientific works on economics. The terms of monitoring introduction into the processes of socio-economic development of a region are defined. The difference between monitoring and standard statistic technology is explained. The fact that socio-economic processes monitoring is primarily directed at collection, examination and preparation of information for making and analyzing of economic decisions at different management levels is proved. The indicators by the direction “renewable energy and energy efficiency”, which are evaluated in the process of monitoring, are outlined. Major tasks of monitoring are defined and principles of its information basis forming are determined.